Upaya Meningkatkan Kompetensi Guru Kelas dalam Proses Pembelajaran Melalui Supervisi Akademik di SDN 9 Cakranegara - Sudiarti, Desak Putu (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2017)
The purpose of this study is to determine the effectiveness of the implementation of academic supervision in an effort to improve the competence of Classroom Teachers in learning in the classroom, whose benefits for the principal is to know the improvement of teacher competence in the learning process. The method of this study used a school action research (PTS) conducted for two cycles, each cycle activity there are four stages of planning, implementation, observation, and reflection. The indicators of success in this study are; 1) School principal observation results and teacher observation during the mentoring process have obtained average score> 4.0, 2) end result> 85% of the number of mentoring participants get average score> 70.00 (good category). The result of the research in the first cycle of principal principal observation (3.80), average teacher observation (3.00) and academic grade teacher supervision score average score (63.67). In the second cycle of principal observation of the average (4.40) with the percentage of achievement (100%), the average teacher observation (4.17) with the percentage of achievement (83.33%) and the results of academic supervision in the target english) average value (81.22) with the percentage of achievement (100%). The success indicator has been reached, the research stated successful and stopped in cycle II. Conclusion; The results of the research on the 2nd cycle showed the improvement of Master’s competence in the learning process in the real class. It is recommended that other Principals conduct similar research in an effort to increase the competence of teachers, and to similar class teachers to conduct learning process in accordance with well-planned scenarios, responsibility, bersunggung-ure for improving student achievement in accordance with the field of study / eyes the lessons he was responsible for.